Los debates sobre la participación de las mujeres en el parlamento brasileño: subrepresentación, la violencia y el acoso - Santos, Polianna Pereira dos; Barcelos, Júlia Rocha de; Gresta, Roberta Maia (Pontificia Universidad Católica del Perú, 2016)
Women were one of the last social groups to conquer political rights in contemporary democracies. Although there are no more legal obstacles for female political participation (active and passive), women’s presence in Brazilian parliaments is minimal. In the Lower House of Parliament (Câmara dos Deputados), after 2014 Elections –that is, 19 years after gender quota regulations in Brazil– women still occupy less than 10% of the seats. That being the case, in this brief study, we revisit cultural, social and institutional variables which are commonly presented as a justification for female under-representation in Brazil. Subsequently, we address gender violence situations which took place in Brazil’s Lower House of Parliament, as well as how they were dealt with by this organization. Furthermore, in attempt to better understand the relations between gender, representation, violence and harassment in the political field, questionnaires were sent to representatives in the Lower House of Parliament, where the two paradigmatic cases which are object of this study took place. In this attempt, we also interview the Vice-Governor of a Brazilian state, a woman who can provide the perspective of the executive branch on the matter. The analysis of these results –including the percentage of answers– should allow us to raise a connection between gender violence in politics and female under-representation.

Las mujeres han sido uno de los últimos contingentes sociales en alcanzar derechos políticos dentro de las democracias contemporáneas. A pesar de no subsistir impedimentos legales para su participación política (activa o pasiva), la presencia de mujeres en el parlamento brasileño es insignificante. En la Cámara de los Diputados, tras las elecciones de 2014 –19 años después de la regulación de las cuotas de género en Brasil– las mujeres todavía ocupan menos del 10% de los asientos. En este breve estudio, se revisan las variables culturales, sociales e institucionales que se presentan comúnmente como justificación para la baja representación femenina en Brasil. Posteriormente, serán revisadas algunas situaciones de violencia de género ocurridas en la Cámara de los Diputados y el trato que se les dio dentro del organismo. Asimismo, en el intento de obtener una idea de la relación entre representación, violencia y acoso político y de género, se enviaron cuestionarios a los miembros del Parlamento Federal, escenario en donde se desarrollaron los dos casos paradigmas que serán estudiados en este trabajo. Con el mismo fin, también se entrevistó a la vicegobernadora del Estado de Piauí-Brasil, que nos proporcionó una perspectiva sobre el tema objeto de estudio en el Poder Ejecutivo. El análisis de dichos resultados –incluyendo los porcentajes de las respuestas– permite delimitar la relación entre violencia de género en la política y laescasa representación femenina.
Debates on female participation in brazilian parlament: underrepresentation, violence and harassment
Keywords: Democracy; Political Rights; Gender; Violence; Democracia; Derechos Políticos; Género; Violencia; https://purl.org/pe-repo/ocde/ford#5.06.00